Majorization for a Class of Analytic Functions Defined by q-Differentiation. (10th July 2014) - Selvakumaran, K. A.; Purohit, Sunil Dutt; Secer, Aydin
Abstract : We introduce a new class of multivalent analytic functions defined by using q -differentiation and fractional q -calculus operators. Further, we investigate majorization properties for functions belonging to this class. Also, we point out some new and known consequences of our main result.